2017
DOI: 10.1038/srep45505
|View full text |Cite
|
Sign up to set email alerts
|

Global evolutionary history and spatio-temporal dynamics of dengue virus type 2

Abstract: DENV-2 spread throughout the tropical and subtropical regions globally, which is implicated in deadly outbreaks of DHF and DSS. Since dengue cases have grown dramatically in recent years, about half of the world’s population is now at risk. Our timescale analysis indicated that the most recent common ancestor existed about 100 years ago. The rate of nucleotide substitution was estimated to be 8.94 × 10−4 subs/site/year. Selection pressure analysis showed that two sites 160 and 403 were under positive selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 61 publications
3
31
0
Order By: Relevance
“…First, we performed in silico analysis to further test the DENV‐host interactions related to the replication cycle in dendritic cells, the primary sentinel human target cell and the primary target for DENV replication and mediated immunity (Marovich et al., ; Schmid, Diamond, & Harris, ). We included DENV Serotype 2 strain 16681 in the in silico analysis (Figure ), which showed that DENV‐2 had a high abundance of predicted N ‐myristoylation sites and that DENV‐2 strains were associated with severe dengue cases and most frequently found in worldwide epidemics (Nunes et al., ; Wei & Li, ). DENV strain 16681 was isolated from a patient with a severe case of dengue fever and has been widely used to study DENV pathogenesis (Okamoto et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we performed in silico analysis to further test the DENV‐host interactions related to the replication cycle in dendritic cells, the primary sentinel human target cell and the primary target for DENV replication and mediated immunity (Marovich et al., ; Schmid, Diamond, & Harris, ). We included DENV Serotype 2 strain 16681 in the in silico analysis (Figure ), which showed that DENV‐2 had a high abundance of predicted N ‐myristoylation sites and that DENV‐2 strains were associated with severe dengue cases and most frequently found in worldwide epidemics (Nunes et al., ; Wei & Li, ). DENV strain 16681 was isolated from a patient with a severe case of dengue fever and has been widely used to study DENV pathogenesis (Okamoto et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…associated with the membrane involved. The difference in multiplicity of infection (MOI) (0.1, 1, 10) with the level of NMT1 expression was MOIdependent were associated with severe dengue cases and most frequently found in worldwide epidemics (Nunes et al, 2016;Wei & Li, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…According to the Brazilian Ministry of Health, a total of 1,455,898 probable dengue cases have been reported in the country from January to September 2019 [7]. The disease is caused by Dengue virus (DENV) (genus Flavivirus, family Flaviviridae), which has four serotypes, characterized by four to six genotypes: DENV-1 (genotypes I, II, III, IV, V, and VI) [8,9], DENV-2 (Asian/American, Asian 1, Asian 2, Cosmopolitan, and American genotypes) [10], DENV-3 (genotypes I-V) [11], and DENV-4 (genotypes I, IIA, IIB, III, IV [sylvatic], and V) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Six distinct DENV-2 genotypes are recognized (Costa et al, 2012;Twiddy et al, 2002;Wei and Li, 2017). The Sylvatic genotype circulates in a sylvatic cycle, while the American, American/Asian, Asian 1, Asian 2 and Cosmopolitan genotypes circulate in urban cycle (Wang et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The Sylvatic genotype circulates in a sylvatic cycle, while the American, American/Asian, Asian 1, Asian 2 and Cosmopolitan genotypes circulate in urban cycle (Wang et al, 2000). Inferred evolutionary relationships of DENV suggest that the urban genotypes evolved from sylvatic lineages due to several crossspecies transmission events into humans, followed by the recent (i.e., early 20th century) evolution of urban forms (Messina et al, 2014;Wang et al, 2000;Wei and Li, 2017). Notably, environmental and social factors such as the introduction of the anthropophilic vector, urbanization, deforestation and the increased human travel and trade have facilitated the emergence, spread and evolution of DENV into human populations (Mayer et al, 2017;Parvez and Parveen, 2017).…”
Section: Introductionmentioning
confidence: 99%